A multi-component synergistic high-performance natural rubber sheet and its industrial preparation method

Through multiple collaborative formulas and modified fiber technology, combined with wet mixing technology, the shortcomings of existing rubber rubber plates in terms of multi-performance comprehensiveness are solved, and high wear resistance, high tear resistance, high strength and low hardness are achieved to meet industrial production needs.

CN119735868AActive Publication Date: 2025-04-01BEIJING HUATENG RUBBER & PLASTIC LATEX PROD CO LTD

Patent Information

Application Number
CN202510239240.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-04-01
Estimated Expiration
2045-03-03

AI Technical Summary

Technical Problem

The existing dry rubber rubber plates are difficult to take into account the characteristics of high wear resistance, high tear resistance, high strength and low hardness, and high performance wet mixing technology can only achieve its comprehensive excellent performance in the laboratory, making it difficult to expand to industrial production.

Method used

The formula of multi-universal synergistic high-performance natural rubber rubber plates, including natural rubber latex, carbon black, nano-silica, modified chopped aramid fiber and other components, is adopted to form a uniform dispersion system and functional interface through wet kneading technology and the coordinated modification of modified fibers, which improves the wear resistance, tear resistance and tensile strength of the rubber plates, and controls hardness.

Benefits of technology

It achieves the unity of high wear resistance, high tear resistance and high strength performance, while maintaining the low hardness and high flexibility of the glue plate, meeting the requirements for comprehensive performance in different industrial fields, and the process route is clear, with good repeatability and controllability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a multi-component synergistic high-performance natural rubber sheet and an industrial preparation method thereof, wherein the multi-component synergistic high-performance natural rubber sheet comprises the following components by weight: 150-175 parts of natural rubber latex, 20-35 parts of carbon black, 7-12 parts of nano-silicon dioxide, 5-10 parts of modified short-cut aramid fiber, 3-5 parts of zinc oxide, 1-1.5 parts of stearic acid, 1-2 parts of vulcanizing agent, 2-5 parts of coupling agent, 1.2-1.8 parts of accelerator, 0.5-1.5 parts of antioxidant and 5-16 parts of auxiliary agent. The invention provides a highly wear-resistant, tear-resistant, high-strength and low-hardness rubber sheet capable of industrial production, including a preparation method of wet-mixed rubber and a feasible industrial large-scale production process preparation complete flow, so as to overcome the shortcomings of existing dry rubber rubber sheets in terms of comprehensive multi-performance and the shortcomings that the current high-performance wet-mixing technology can only achieve its comprehensive excellent performance in the laboratory.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of rubber materials, and in particular to a multi-component synergistic high-performance natural rubber sheet and an industrial preparation method thereof. Background Art

[0002] In many industrial fields, such as machinery manufacturing, mining, transportation, etc., there are strict requirements on the performance of rubber sheets. Traditional dry rubber sheets often have difficulty in taking into account multiple characteristics such as high wear resistance, high tear resistance, high strength and low hardness. In addition, some similar high wear resistance and high tear resistance wet mixing technologies in China can only achieve their comprehensive excellent performance in the laboratory. When expanded to industrial production, all performances are greatly reduced, and the large-scale production process route is imperfect and cannot meet the needs of the market. For example, rubber parts used in mining equipment require high wear resistance and high tear resistance to cope with the impact and friction of ore, but the existing products have a high hardness and are easy to cause damage to other parts of the equipment. In addition, due to stress concentration during long-term use, they are torn or damaged, which cannot meet the production needs of high efficiency, safety and long life; in the field of sanitation sweeper manufacturing, rubber sheets are used in scrapers and other parts, which require low hardness, high elasticity and high tear resistance, as well as high wear resistance to maintain a longer service life and reduce the cost of use. However, the current rubber sheets are not satisfactory in terms of the comprehensive performance of these properties. Therefore, it is urgent to develop a multi-functional synergistic high-performance rubber sheet that can be smoothly promoted to industrial production. Summary of the invention

[0003] The present invention aims to provide a rubber sheet with high wear resistance, high tear resistance, high strength and low hardness that can be industrially produced, including a preparation method of wet mixed rubber and a feasible industrial large-scale production process to prepare a complete process, so as to overcome the shortcomings of existing dry rubber sheets in terms of comprehensive multi-performance and the shortcomings that the current high-performance wet mixing technology can only achieve its comprehensive excellent performance in the laboratory, and provide a perfect solution for R&D conversion. Meet the special needs of various industrial fields for rubber materials and improve the quality and performance of related products.

[0004] The present invention is implemented by the following technical solutions: On the one hand, the present invention discloses a multi-component synergistic high-performance natural rubber sheet, which comprises the following components by weight: 150-175 parts of natural rubber latex, 20-35 parts of carbon black, 7-12 parts of nano silicon dioxide, 5-10 parts of modified short-cut aramid fiber, 3-5 parts of zinc oxide, 1-1.5 parts of stearic acid, 1-2 parts of vulcanizing agent, 2-5 parts of coupling agent, 1.2-1.8 parts of accelerator, 0.5-1.5 parts of antioxidant and 5-16 parts of auxiliary agent.

[0005] Furthermore, the solid content of the natural rubber latex is 60±2%.

[0006] Furthermore, the preparation method of the modified chopped aramid fiber specifically comprises the following steps: (1) Pretreatment of chopped aramid fibers: The cleaned and dried chopped aramid fibers were immersed in a 2 wt % sodium hydroxide solution at 40° C. for 15 min, then washed to neutrality and dried to obtain pretreated chopped aramid fibers; (2) Dopamine modification: dopamine is added to a buffer solution to prepare a dopamine solution with a concentration of 1-3.5 g / L, the pH of the dopamine solution is adjusted to 8.3-8.8 with an inorganic base, the pretreated chopped aramid fibers are immersed in the dopamine solution, and the fibers are allowed to stand overnight at room temperature. After being taken out, they are washed and dried to obtain dopamine-modified chopped aramid fibers. (3) In situ growth of LDHs: prepare a precursor solution of 0.04-0.06 mol / L Mg(NO3)2·6H2O, 0.02-0.03 mol / L Al(NO3)3·9H2O and 0.4-0.5 mol / L urea, immerse the dopamine-modified chopped aramid fibers in the precursor solution, place in a closed reactor, heat to 85-90°C under nitrogen protection, stir at a low speed, react for 4-12 h, and after the reaction is completed, wash and dry to obtain the modified chopped aramid fibers.

[0007] Furthermore, the length of the chopped aramid fibers is 0.5-3 mm.

[0008] Furthermore, the buffer solution in step (2) is any one of Tris-HCl, disodium hydrogen phosphate-potassium dihydrogen phosphate buffer solution, disodium hydrogen phosphate-sodium dihydrogen phosphate buffer solution or potassium dihydrogen phosphate-sodium hydroxide buffer solution.

[0009] Furthermore, in step (3), the stirring rate is 100-180 r / min.

[0010] Further, the vulcanizing agent is vulcanizing agent S-80; The coupling agent is silane coupling agent Si-69; The accelerator is composed of accelerator TBBS and accelerator DPG in a mass ratio of 1:2; The antioxidant is composed of antioxidant RD and antioxidant 4020 in a mass ratio of 1:1.5.

[0011] Furthermore, the auxiliary agent is composed of emulsified cycloalkane oil and emulsified aromatic oil in a mass ratio of 4:1.

[0012] The second aspect of the present invention discloses a method for preparing the multi-component synergistic high-performance natural rubber sheet, comprising the following steps: S1. Add carbon black and nano-silica to deionized water, continue to add silane coupling agent, high-speed shear dispersion to form a uniform slurry, continue to add modified chopped aramid fiber, stir and disperse at low speed to obtain a filler slurry; S2. The natural rubber latex and additives are mixed evenly, filler slurry, zinc oxide and stearic acid are added, stirred evenly, accelerators and antioxidants are added successively, and stirring is continued to obtain a mixed latex; S3. Add calcium chloride solution as a coagulant to the mixed latex, stir until the colloid flocculates, filter, wash, and dry to obtain a rubber masterbatch; S4. The rubber masterbatch was added to an internal mixer, mixed at room temperature for 5-10 min, a vulcanizing agent was added, and mixing was continued for 5-10 min to obtain a uniformly mixed rubber, and the rubber was calendered or extruded to form a rubber sheet blank; S5. The rubber sheet blank is fed into a vulcanizing press for vulcanization and molding to obtain a multi-component synergistic high-performance natural rubber sheet.

[0013] Furthermore, in step S1, the rotation speed of the high-speed shear dispersion is 8000-10000 r / min, and the shear dispersion time is 30-40 min; the rotation speed of the low-speed stirring is 150-200 r / min, and the stirring time is 10-20 min; The concentration of the calcium chloride solution in step S3 is 5wt%; In step S5, the vulcanization temperature is 120-160° C. and the pressure is 15 MPa.

[0014] Beneficial effects of the present invention: 1. The conventional carbon black filler and nano-silica are added in a coordinated manner in the present invention to form a uniform dispersion system in the rubber matrix, thereby improving the wear resistance and tear resistance of the rubber sheet. The short-cut aramid fiber is modified by LDHs / dopamine synergistically to form a functional layer on the fiber surface, improve the interface bonding with the rubber matrix, effectively transfer stress, further improve the overall impact resistance and tensile strength, and at the same time control the vulcanization network structure to keep the rubber sheet at a low hardness.

[0015] 2. The present invention adopts wet mixing technology, and by directly dispersing each component in the rubber emulsion, the problem of filler agglomeration in traditional dry mixing is avoided, and the dispersion uniformity is significantly improved, especially the dispersion effect on nano-scale fillers is more prominent. In addition, the compounded accelerator and antioxidant system provides excellent vulcanization characteristics and aging protection capabilities. The compounding of cyclohexane oil and aromatic oil not only improves the processing performance of the rubber compound, but also improves the dynamic performance of the product to a certain extent. This multi-component synergistic formula design and innovative preparation process not only achieves wear resistance, tear resistance and high strength performance, but also maintains the low hardness and high flexibility of the rubber sheet, thereby meeting the requirements for comprehensive performance in different fields. DETAILED DESCRIPTION

[0016] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following embodiments.

[0017] In the examples and comparative examples of the present invention, the solid content of the natural rubber latex is 60±2%; The vulcanizing agent is vulcanizing agent S-80; The coupling agent is silane coupling agent Si-69; The accelerator is composed of accelerator TBBS and accelerator DPG in a mass ratio of 1:2; The antioxidant is composed of antioxidant RD and antioxidant 4020 in a mass ratio of 1:1.5; The auxiliary agent is composed of emulsified cyclohexane oil and emulsified aromatic oil in a mass ratio of 4:1.

[0018] Example 1 A multi-component synergistic high-performance natural rubber sheet comprises the following components by weight: 160 parts of natural rubber latex, 30 parts of carbon black, 10 parts of nano-silicon dioxide, 8 parts of modified chopped aramid fiber, 4 parts of zinc oxide, 1.2 parts of stearic acid, 1.5 parts of vulcanizing agent, 3 parts of coupling agent, 1.5 parts of accelerator, 1.0 parts of antioxidant and 12 parts of auxiliary agent.

[0019] The preparation of modified chopped aramid fiber specifically includes the following steps: (1) Pretreatment of chopped aramid fibers: The cleaned and dried chopped aramid fibers (length 2-3 mm) were immersed in a 2 wt % sodium hydroxide solution at 40 ° C for 15 min, then washed to neutrality and dried to obtain pretreated chopped aramid fibers; (2) Dopamine modification: dopamine is added to a disodium hydrogen phosphate-potassium dihydrogen phosphate buffer solution to prepare a dopamine solution with a concentration of 2.0 g / L. The pH of the dopamine solution is adjusted to 8.5 with an inorganic base. The pretreated chopped aramid fibers are immersed in the dopamine solution and allowed to stand at room temperature overnight. After being taken out, they are washed and dried to obtain dopamine-modified chopped aramid fibers. (3) In situ growth of LDHs: Prepare a precursor solution of 0.06 mol / L Mg(NO3)2·6H2O, 0.03 mol / L Al(NO3)3·9H2O and 0.45 mol / L urea, immerse the dopamine-modified chopped aramid fibers in the precursor solution, place in a closed reactor, heat to 90 °C under nitrogen protection, stir at 120 r / min, and react for 6 h. After the reaction is completed, wash and dry to obtain the modified chopped aramid fibers.

[0020] The preparation method of the multi-component synergistic high-performance natural rubber sheet comprises the following steps: S1. Add carbon black and nano-silica to deionized water, continue to add silane coupling agent, 10000r / min high-speed shear dispersion for 30min to form a uniform slurry, continue to add modified short chopped aramid fiber, 150r / min stirring dispersion for 20min to obtain a filler slurry; S2. The natural rubber latex and additives are mixed evenly, filler slurry, zinc oxide and stearic acid are added, stirred evenly, accelerators and antioxidants are added successively, and stirring is continued to obtain a mixed latex; S3. Add 5wt% calcium chloride solution as a coagulant to the mixed latex, stir until the colloid flocculates, filter, wash, and dry to obtain a rubber masterbatch; S4. The rubber masterbatch was added to an internal mixer and mixed at room temperature for 10 min, a vulcanizing agent was added, and mixing was continued for 10 min to obtain a uniformly mixed rubber, and the rubber was calendered into a rubber sheet having a thickness of 1.8 mm and a width of 250 mm. S5. The rubber sheet blank is fed into a vulcanizing press, and the vulcanizing temperature is set to 150°C, the pressure is 15 MPa, the vulcanizing time is T90+3min, and the vulcanization is performed to obtain a multi-component synergistic high-performance natural rubber sheet.

[0021] Example 2 A multi-component synergistic high-performance natural rubber sheet comprises the following components by weight: 160 parts of natural rubber latex, 27 parts of carbon black, 9 parts of nano-silicon dioxide, 10 parts of modified chopped aramid fiber, 4 parts of zinc oxide, 1.2 parts of stearic acid, 1.5 parts of vulcanizing agent, 3 parts of coupling agent, 1.5 parts of accelerator, 1.0 parts of antioxidant and 12 parts of auxiliary agent.

[0022] The preparation methods of the modified chopped aramid fibers and the multi-component synergistic high-performance natural rubber sheet are the same as those in Example 1.

[0023] Example 3 A multi-component synergistic high-performance natural rubber sheet comprises the following components by weight: 160 parts of natural rubber latex, 33 parts of carbon black, 11 parts of nano-silicon dioxide, 6 parts of modified chopped aramid fiber, 4 parts of zinc oxide, 1.2 parts of stearic acid, 1.5 parts of vulcanizing agent, 3 parts of coupling agent, 1.5 parts of accelerator, 1.0 parts of antioxidant and 12 parts of auxiliary agent.

[0024] The preparation methods of the modified chopped aramid fibers and the multi-component synergistic high-performance natural rubber sheet are the same as those in Example 1.

[0025] Based on Examples 1-3, further, when the pH of the dopamine solution is adjusted to 8.5 with an inorganic base, the pH is adjusted to 8.5 by the following steps: Obtaining a preset number of specific portions of inorganic base from the inorganic base to obtain a plurality of small portions of inorganic base; Adding small portions of inorganic base to the dopamine solution in sequence, and after each addition of the small portion of inorganic base to the dopamine solution, monitoring the pH value of the dopamine solution in real time to obtain pH change information of the dopamine solution, thereby obtaining pH change information of the dopamine solution; Analyzing the data of the pH change after the addition of a small amount of inorganic base to the dopamine solution after the pH change is stabilized according to the pH change information of the dopamine solution, determining a plurality of pH adjustment data, and obtaining the first pH data; wherein the pH adjustment data is the pH data of the pH change after the addition of a small amount of inorganic base to the dopamine solution after the pH change is stabilized; Analyzing the pH change characteristics of the dopamine solution during the pH adjustment process according to the first pH data to obtain the pH adjustment characteristics includes: Calculate the PH difference of the PH adjustment data in the first PH data and the adjacent PH adjustment data to obtain PH change data; Analyze the change rules of the PH change data, determine the change characteristics of the PH change data, and obtain the first PH adjustment characteristics; The pH change data is combined with the amount of the small portion of inorganic alkali to perform change characteristic analysis to obtain sub-change data characteristics, and the sub-change data characteristics are formed into a target analysis data sequence according to the acquisition order of the pH change data; In the target analysis data sequence, the first two, three, ..., N data are analyzed for change characteristics respectively to determine multiple data change sub-characteristics; wherein N is the number of sub-change data characteristics in the target analysis data sequence; Perform change rule analysis according to the multiple data change sub-features, determine the change characteristics of the data change sub-features, and obtain a second PH adjustment feature; Analyzing whether the first PH adjustment feature and the second PH adjustment feature are the same, if the first PH adjustment feature and the second PH adjustment feature are the same, the first PH adjustment feature or the second PH adjustment feature is the final PH adjustment feature, if the first PH adjustment feature and the second PH adjustment feature are different, comprehensively analyzing the first PH adjustment feature and the second PH adjustment feature, determining a third PH adjustment feature, and using the third PH adjustment feature as the final PH adjustment feature; Obtain the current pH data of the dopamine solution, analyze the difference between the current pH data and 8.5, and obtain the target pH difference; According to the pH adjustment characteristics, the target pH difference and the preset fine-tuning threshold are combined to obtain the inorganic base again to obtain the target amount of inorganic base; Adding a target amount of inorganic base to the dopamine solution, obtaining pH data after the pH change stabilizes, and obtaining second pH data; Fine-tune based on the second pH data, add a small amount of inorganic base to the dopamine solution, wait for a while to obtain the pH data of the dopamine solution, obtain the pH fine-tuning data, and repeat multiple times until the pH fine-tuning data is equal to 8.5.

[0026] The above technical scheme can not only improve the efficiency of adjusting the pH value of the dopamine solution, but also ensure the accuracy of the pH adjustment, thereby ensuring the properties of the dopamine solution and providing a guarantee for immersing the pretreated chopped aramid fibers in the dopamine solution, thereby better obtaining dopamine-modified chopped aramid fibers, improving the quality of the modified chopped aramid fibers, and further forming a functional layer on the fiber surface, thereby improving the interface bonding with the rubber matrix, effectively transferring stress, and further improving the overall impact resistance and tensile strength, while controlling the vulcanization network structure to keep the rubber sheet at a relatively low hardness. By using multiple small portions of inorganic alkali, we can gain a preliminary understanding of the characteristics of the pH change of the dopamine solution when adjusting the pH, so that the pH can be adjusted according to the pH adjustment characteristics. The pH can be adjusted in two stages: target amount of inorganic alkali and fine-tuning. This not only allows the pH of the dopamine solution to quickly approach the target pH (8.5), but also avoids one-time excessive adjustment that causes the pH of the dopamine solution to exceed the target pH, reduces the time for pH adjustment, and improves the efficiency of pH adjustment of the dopamine solution. At the same time, with the help of a preset fine-tuning threshold, excessive pH adjustment can be avoided, which may cause the dopamine solution to fail to meet the requirements due to exceeding the target pH, thereby reducing unnecessary waste of time and resources. In addition, when analyzing the pH change characteristics of the dopamine solution during the adjustment process based on the first pH data, two methods are used to obtain the first pH adjustment characteristic and the second pH adjustment characteristic respectively, and then the final pH adjustment characteristic is determined, which reduces the large error of the pH adjustment characteristic caused by one-sided factors and improves the accuracy of the pH adjustment characteristic, thereby providing a guarantee for obtaining the inorganic base again according to the pH adjustment characteristic combined with the target pH difference and the preset fine-tuning threshold, improving the suitability of the target amount of inorganic base, and then improving the adjustment effect of the target amount of inorganic base in subsequent adjustments, so that when the target amount of inorganic base and fine-tuning are used to continue to adjust the pH in two stages, the pH adjustment can be performed more efficiently.

[0027] Furthermore, when the carbon black and nano-silicon dioxide are added to deionized water and the silane coupling agent is added, a detection device is used to perform detection and analysis on the slurry during a 10000 r / min high-speed shear dispersion process, including: Perform time statistics on the high-speed shear dispersion process to obtain the high-speed shear dispersion statistical time, and obtain the slurry status information in real time to obtain the slurry real-time status information; Analyze the slurry dispersion according to the real-time status information of the slurry to determine whether the slurry is evenly dispersed and obtain the slurry analysis results; When the slurry analysis result shows that the slurry is unevenly dispersed, analyze and determine whether the high-speed shear dispersion statistical time has reached the preset time. If the high-speed shear dispersion statistical time has reached the preset time, an uneven slurry dispersion warning is issued. If the high-speed shear dispersion statistical time has not reached the preset time, continue to perform 10000r / min high-speed shear dispersion until the high-speed shear dispersion statistical time has reached the preset time, or the slurry analysis result shows that the slurry is evenly dispersed. When the slurry analysis result shows that the slurry is evenly dispersed, continue to perform high-speed shear dispersion at 10000r / min according to the preset blending time, then stop the high-speed shear dispersion, obtain the statistical time of the high-speed shear dispersion at this time, obtain the current statistical time of the high-speed shear dispersion, analyze the difference between the current statistical time of the high-speed shear dispersion and the preset time, obtain the target surplus time, and then give a prompt for the target surplus time.

[0028] The above-mentioned detection and analysis of the slurry during the 10000r / min high-speed shear dispersion process by the detection device ensures that the slurry is evenly dispersed after the carbon black and nano-silica are added to the deionized water and the silane coupling agent is further added, thereby providing convenient conditions for adding modified chopped aramid fibers to the slurry, ensuring the properties of the filler slurry, avoiding agglomeration of the filler slurry, and thereby improving the performance of the multi-synergistic high-performance natural rubber sheet. By performing time statistics on the high-speed shear dispersion process, the 10000r / min high-speed shear dispersion time can be measured to avoid wasting time and resources caused by long-term high-speed shear dispersion. At the same time, by analyzing the slurry dispersion situation, the final slurry dispersion is guaranteed to be uniform, and the uneven slurry dispersion will not affect the subsequent use of the slurry. When the slurry analysis result shows that the slurry dispersion is uneven, the preset time (30min) is combined with the preset time to issue an uneven slurry dispersion warning, so that relevant personnel can understand the situation after the 10000r / min high-speed shear dispersion process ends, so that the slurry can be processed again according to the actual situation. At the same time, when the slurry analysis result shows that the slurry dispersion is uniform, the blending time is used to further ensure that the slurry is fully dispersed. By analyzing the difference between the current statistical time and the preset time of the high-speed shear dispersion, the gap between the preset time (30min) and the actually required high-speed shear dispersion time is clarified, reducing unnecessary time waste. At the same time, the preset time for the subsequent 10000r / min high-speed shear dispersion can also be optimized.

[0029] Comparative Example 1 In this comparative example, no modified chopped aramid fiber was added.

[0030] A natural rubber sheet comprises the following components by weight: 160 parts of natural rubber latex, 30 parts of carbon black, 10 parts of nano silicon dioxide, 4 parts of zinc oxide, 1.2 parts of stearic acid, 1.5 parts of vulcanizing agent, 3 parts of coupling agent, 1.5 parts of accelerator, 1.0 parts of antioxidant and 12 parts of auxiliary agent.

[0031] The method for preparing a natural rubber sheet comprises the following steps: S1. Add carbon black and nano-silica to deionized water, continue to add silane coupling agent, and disperse at a high speed of 10000r / min for 30min to obtain a filler slurry; S2. The natural rubber latex and additives are mixed evenly, filler slurry, zinc oxide and stearic acid are added, stirred evenly, accelerators and antioxidants are added successively, and stirring is continued to obtain a mixed latex; S3. Add 5wt% calcium chloride solution as a coagulant to the mixed latex, stir until the colloid flocculates, filter, wash, and dry to obtain a rubber masterbatch; S4. The rubber masterbatch was added to an internal mixer and mixed at room temperature for 10 min, a vulcanizing agent was added, and mixing was continued for 10 min to obtain a uniformly mixed rubber, and the rubber was calendered into a rubber sheet having a thickness of 1.8 mm and a width of 250 mm. S5. The rubber sheet blank is fed into a vulcanizing press, and the vulcanizing temperature is set to 150°C, the pressure is 15 MPa, and the vulcanizing time is T90+3min. The natural rubber sheet is obtained by vulcanization molding.

[0032] Comparative Example 2 In this comparative example, unmodified chopped aramid fibers were added.

[0033] A natural rubber sheet comprises the following components by weight: 160 parts of natural rubber latex, 30 parts of carbon black, 10 parts of nano silicon dioxide, 8 parts of short-cut aramid fiber, 4 parts of zinc oxide, 1.2 parts of stearic acid, 1.5 parts of vulcanizing agent, 3 parts of coupling agent, 1.5 parts of accelerator, 1.0 parts of antioxidant and 12 parts of auxiliary agent.

[0034] The preparation method of the multi-component synergistic high-performance natural rubber sheet comprises the following steps: S1. Add carbon black and nano-silica to deionized water, continue to add silane coupling agent, 10000r / min high-speed shear dispersion for 30min to form a uniform slurry, continue to add short-cut aramid fiber, 150r / min stirring dispersion for 20min to obtain a filler slurry; S2. The natural rubber latex and additives are mixed evenly, filler slurry, zinc oxide and stearic acid are added, stirred evenly, accelerators and antioxidants are added successively, and stirring is continued to obtain a mixed latex; S3. Add 5wt% calcium chloride solution as a coagulant to the mixed latex, stir until the colloid flocculates, filter, wash, and dry to obtain a rubber masterbatch; S4. The rubber masterbatch was added to an internal mixer and mixed at room temperature for 10 min, a vulcanizing agent was added, and mixing was continued for 10 min to obtain a uniformly mixed rubber, and the rubber was calendered into a rubber sheet having a thickness of 1.8 mm and a width of 250 mm. S5. The rubber sheet blank is fed into a vulcanizing press, and the vulcanizing temperature is set to 150°C, the pressure is 15 MPa, the vulcanizing time is T90+3min, and the vulcanization is performed to obtain a multi-component synergistic high-performance natural rubber sheet.

[0035] Comparative Example 3 Dopamine-modified chopped aramid fibers were added in this comparative example.

[0036] A multi-component synergistic high-performance natural rubber sheet comprises the following components by weight: 160 parts of natural rubber latex, 30 parts of carbon black, 10 parts of nano-silicon dioxide, 8 parts of modified chopped aramid fiber A, 4 parts of zinc oxide, 1.2 parts of stearic acid, 1.5 parts of vulcanizing agent, 3 parts of coupling agent, 1.5 parts of accelerator, 1.0 parts of antioxidant and 12 parts of auxiliary agent.

[0037] The preparation of modified chopped aramid fiber A specifically comprises the following steps: (1) Pretreatment of chopped aramid fibers: The cleaned and dried chopped aramid fibers (length 2-3 mm) were immersed in a 2 wt % sodium hydroxide solution at 40 ° C for 15 min, then washed to neutrality and dried to obtain pretreated chopped aramid fibers; (2) Dopamine modification: dopamine was added to a disodium hydrogen phosphate-potassium dihydrogen phosphate buffer solution to prepare a dopamine solution with a concentration of 2.0 g / L. The pH of the dopamine solution was adjusted to 8.5 with an inorganic base. The pretreated chopped aramid fibers were immersed in the dopamine solution and allowed to stand at room temperature overnight. After being taken out, they were washed and dried to obtain modified chopped aramid fibers A.

[0038] The preparation method of the multi-component synergistic high-performance natural rubber sheet comprises the following steps: S1. Add carbon black and nano-silica to deionized water, continue to add silane coupling agent, 10000r / min high-speed shear dispersion for 30min to form a uniform slurry, continue to add modified chopped aramid fiber A, 150r / min stirring dispersion for 20min to obtain a filler slurry; S2. The natural rubber latex and additives are mixed evenly, filler slurry, zinc oxide and stearic acid are added, stirred evenly, accelerators and antioxidants are added successively, and stirring is continued to obtain a mixed latex; S3. Add 5wt% calcium chloride solution as a coagulant to the mixed latex, stir until the colloid flocculates, filter, wash, and dry to obtain a rubber masterbatch; S4. The rubber masterbatch was added to an internal mixer and mixed at room temperature for 10 min, a vulcanizing agent was added, and mixing was continued for 10 min to obtain a uniformly mixed rubber, and the rubber was calendered into a rubber sheet having a thickness of 1.8 mm and a width of 250 mm. S5. The rubber sheet blank is fed into a vulcanizing press, and the vulcanizing temperature is set to 150°C, the pressure is 15 MPa, the vulcanizing time is T90+3min, and the vulcanization is performed to obtain a multi-component synergistic high-performance natural rubber sheet.

[0039] Test example The performance tests of the natural rubber sheets prepared in Examples 1-3 and Comparative Examples 1-3 were performed, and the results are shown in Table 1.

[0040] Hardness: Refer to GB / T 531.1-2008 Shore hardness test method for vulcanized rubber or thermoplastic rubber; Rotating roller abrasion: Refer to GB / T 9867-2008 Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrasion machine method); Tear strength: Refer to standard GB / T 529-2008 Determination of tear strength of vulcanized rubber or thermoplastic rubber (trouser-shaped, right-angled and crescent-shaped specimens); Tensile strength and elongation at break: refer to standard GB / T 528-2009 Test of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber.

[0041] Table 1 Performance test results of natural rubber sheets prepared in Examples 1-3 and Comparative Examples 1-3 Group Hardness Rotating drum wear (mg / 40m) Tear strength (KN / m) Tensile strength (MPa) Elongation at break (%) Example 1 40 136 73 23 930 Example 2 37 135 75 24 910 Example 3 42 139 69 21 900 Comparative Example 1 38 168 52 17 840 Comparative Example 2 40 154 57 18 860 Comparative Example 3 39 149 63 20 870 It can be seen from the results in Table 1 that the performance indicators of Examples 1-3 are significantly better than those of Comparative Examples 1-3, which fully confirms the feasibility and advancement of the technical solution of the present invention. The natural rubber sheet prepared by the method of the present invention achieves the unity of high strength, high wear resistance and low hardness, which is difficult to take into account in traditional formulas.

[0042] In the present invention, the dopamine and LDHs dual modification process is used to treat the chopped aramid fibers. From the data of Comparative Examples 2 and 3, it can be seen that the reinforcement effect of the unmodified fibers or the fibers modified only with dopamine is obviously inferior to that of the dual modification (Examples 1-3). This is because the dopamine modification provides preliminary interfacial activity, and the in-situ growth of LDHs builds a more complex interfacial structure on this basis. The synergistic effect of the two significantly improves the interfacial bonding strength between the fiber and the rubber matrix.

[0043] In addition, the composite reinforcement system of carbon black and nano-silicon dioxide used in the present invention exhibits a good synergistic effect. The data comparison of Examples 1-3 shows that by adjusting the ratio of modified fiber, carbon black and nano-silicon dioxide, the material properties can be regulated within a certain range. This provides a practical formula optimization range, which has important guiding significance. From the perspective of industrial application, this solution not only achieves a comprehensive improvement in performance indicators, but also has a clear process route and good repeatability and controllability.

[0044] Finally, it should be noted that the above-mentioned embodiments only express several implementation methods of the present invention and are not intended to limit the invention. For those skilled in the art, any modification, equivalent replacement, improvement, etc. made without departing from the concept of the present invention should be included in the protection scope of the invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A multi-component synergistic high-performance natural rubber sheet, characterized in that: The composition comprises the following components by weight: 150-175 parts of natural rubber latex, 20-35 parts of carbon black, 7-12 parts of nano silicon dioxide, 5-10 parts of modified chopped aramid fiber, 3-5 parts of zinc oxide, 1-1.5 parts of stearic acid, 1-2 parts of vulcanizing agent, 2-5 parts of coupling agent, 1.2-1.8 parts of accelerator, 0.5-1.5 parts of antioxidant and 5-16 parts of auxiliary agent.

2. The multi-component synergistic high-performance natural rubber sheet according to claim 1, characterized in that: The solid content of the natural rubber latex is 60±2%.

3. The multi-component synergistic high-performance natural rubber sheet according to claim 1, characterized in that: The preparation method of the modified chopped aramid fiber specifically comprises the following steps: (1) Pretreatment of chopped aramid fibers: The cleaned and dried chopped aramid fibers were immersed in a 2 wt % sodium hydroxide solution at 40° C. for 15 min, then washed to neutrality and dried to obtain pretreated chopped aramid fibers; (2) Dopamine modification: dopamine is added to a buffer solution to prepare a dopamine solution with a concentration of 1-3.5 g / L, the pH of the dopamine solution is adjusted to 8.3-8.8 with an inorganic base, the pretreated chopped aramid fibers are immersed in the dopamine solution, and the fibers are allowed to stand overnight at room temperature. After being taken out, they are washed and dried to obtain dopamine-modified chopped aramid fibers. (3) In situ growth of LDHs: prepare a precursor solution of 0.04-0.06 mol / L Mg(NO3)2·6H2O, 0.02-0.03 mol / L Al(NO3)3·9H2O and 0.4-0.5 mol / L urea, immerse the dopamine-modified chopped aramid fibers in the precursor solution, place in a closed reactor, heat to 85-90°C under nitrogen protection, stir at a low speed, react for 4-12 h, and after the reaction is completed, wash and dry to obtain the modified chopped aramid fibers.

4. The multi-component synergistic high-performance natural rubber sheet according to claim 3, characterized in that: The length of the chopped aramid fibers is 0.5-3 mm.

5. The multi-component synergistic high-performance natural rubber sheet according to claim 3, characterized in that: The buffer solution in step (2) is any one of Tris-HCl, disodium hydrogen phosphate-potassium dihydrogen phosphate buffer solution, disodium hydrogen phosphate-sodium dihydrogen phosphate buffer solution or potassium dihydrogen phosphate-sodium hydroxide buffer solution.

6. The multi-component synergistic high-performance natural rubber sheet according to claim 3, characterized in that: The stirring rate in step (3) is 100-180 r / min.

7. The multi-component synergistic high-performance natural rubber sheet according to claim 1, characterized in that: The vulcanizing agent is vulcanizing agent S-80; The coupling agent is silane coupling agent Si-69; The accelerator is composed of accelerator TBBS and accelerator DPG in a mass ratio of 1:2; The antioxidant is composed of antioxidant RD and antioxidant 4020 in a mass ratio of 1:1.

5.

8. The multi-component synergistic high-performance natural rubber sheet according to claim 1, characterized in that: The auxiliary agent is composed of emulsified cycloalkane oil and emulsified aromatic oil in a mass ratio of 4:

1.

9. A method for preparing a multi-component synergistic high-performance natural rubber sheet as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Add carbon black and nano-silica to deionized water, continue to add silane coupling agent, high-speed shear dispersion to form a uniform slurry, continue to add modified chopped aramid fiber, stir and disperse at low speed to obtain a filler slurry; S2. The natural rubber latex and additives are mixed evenly, filler slurry, zinc oxide and stearic acid are added, stirred evenly, accelerators and antioxidants are added successively, and stirring is continued to obtain a mixed latex; S3. Add calcium chloride solution as a coagulant to the mixed latex, stir until the colloid flocculates, filter, wash, and dry to obtain a rubber masterbatch; S4. The rubber masterbatch was added to an internal mixer, mixed at room temperature for 5-10 min, a vulcanizing agent was added, and mixing was continued for 5-10 min to obtain a uniformly mixed rubber, and the rubber was calendered or extruded to form a rubber sheet blank; S5. The rubber sheet blank is fed into a vulcanizing press for vulcanization and molding to obtain a multi-component synergistic high-performance natural rubber sheet.

10. The method for preparing the multi-component synergistic high-performance natural rubber sheet according to claim 9, characterized in that: In step S1, the rotation speed of high-speed shear dispersion is 8000-10000 r / min, and the shear dispersion time is 30-40 min; the rotation speed of low-speed stirring is 150-200 r / min, and the stirring time is 10-20 min; The concentration of the calcium chloride solution in step S3 is 5wt%; In step S5, the vulcanization temperature is 120-160° C. and the pressure is 15 MPa.

Citation Information

Patent Citations

  • Surface modification method for lossless environment-friendly convenient aramid fiber material

    CN102758357A

  • Surface-modified aramid fiber and preparation method thereof

    CN105862396A

  • Low-heat-generation high-wear-resistance tear-resistant engineering tire tread rubber and preparation method thereof

    CN115160659A

  • Impact-resistant flame-retardant conveyor belt cover rubber for steel wire rope core for coal mine and preparation method thereof

    CN119176976A

  • Dendritic silver-plated aramid electrically conductive filler and preparation method therefor and application thereof, and polymer / dendritic silver-plated aramid composite material

    WO2023082090A1

Cited By

  • Wear-resistant sealing rubber strip and preparation method thereof

    CN120923928A